Dietary citrulline supplementation enhances milk production in lactating dairy goats - Arianna N. Lopez; Makenzie G. Newton; Claire Stenhouse; Erin Connolly; Karina L. Hissen; Scott Horner; Guoyao Wu; William Foxworth; Fuller W. Bazer (Journal of Animal Science and Biotechnology)
Abstract Background Lactational performance depends heavily on age, health, and nutrition. L-Citrulline (Cit) is an effective precursor of L-arginine (Arg), an amino acid that has important roles in synthesis of nitric oxide (NO) and polyamines. Ruminal microbes degrade extracellular Arg; however, extracellular L-citrulline (Cit) is not degraded by ruminal microbes due to lack of uptake and can be fed unencapsulated as a precursor for Arg. As NO is a vasodilator, an increase in blood flow and transport of molecules to mammary tissue may enhance lactational performance and milk composition. Increases in polyamine production may increase milk protein synthesis within mammary tissue, thus increasing milk protein content. This study determined, for the first time, effects of dietary Cit supplementation on milk production and milk composition of Alpine dairy goats. Methods Does were synchronized to estrus and bred to Alpine bucks. Parturition was induced on d 149 of gestation and does were suckled overnight allowing kid(s) to obtain colostrum before being milked 24 h later (d 1 of lactation). Does were assigned to either control (CON, n = 24) or Cit (CIT, n = 23) diets. The isonitrogenous control diet consisted of 97.63% basal diet and 2.37% supplement (1.37% L-alanine and 1.00% soybean hydrogenated oil). The CIT supplemented diet consisted of 97.63% basal diet and 2.37% supplement (0.5% Cit, 0.5% L-glutamine, 1% soybean hydrogenated oil, 0.37% cornstarch). Diets were group fed ad-libitum by treatment group. Blood samples were collected on d 0 and 30 of lactation, milk volumes measured twice daily, and on d 10, 20, and 40 of lactation, milk samples were collected. Results CIT-treated does had greater daily milk production (P < 0.05) and there was an effect of day of lactation on daily milk production (P < 0.0001). Sire had significant effect on daily milk production as well (P < 0.05). Milk compositional analyses revealed Cit supplementation increased solid-non-fat (SNF; P < 0.05) and protein (P < 0.05) content in milk. Conclusions Our novel results indicate that dietary supplementation of Cit fed ad-libitum in Alpine does increased daily milk yield, milk SNF content, and protein content. Supplemental Cit may be a proxy for Arg in goats to enhance lactational performance.